Relationship between mindfulness, resilience, work-family conflict and job performance among working adults in Malaysia - Cheah, Jie Min; Lott, Sin Yee; Teoh, Yi Wen (2023)
Job performance is defined as the measurement of a working adult’s productivity in the workplace. Recent research has revealed an increasing interest in the elements influencing work performance, an important component for every organization. Lately, resilience, work-family conflict and mindfulness have been factors found to affect job performance among working adults. Thus, this quantitative correlational research aims to study the relationship between the aforementioned predictors (resilience, work-family conflict and mindfulness) towards job performance among working adults in Malaysia. 95 participants were recruited in this study through the purposive sampling method. Working adults in UTAR and UTAR Hospital, aged between 21 to 60 years old (M = 36) with an unequal number of male and female participants, were recruited in this study. Qualtrics survey forms were circulated online and physically using paper and pencil. The results of Pearson’s Product Moment Correlation (PPMC) showed that mindfulness significantly and positively correlated with job performance, whereas work-family conflict significantly and negatively correlated with job performance. However, resilience is not significantly correlated with job performance. On the other hand, the results of Multiple Linear Regression (MLR) further indicated that mindfulness and work-family conflict were meaningful positive and negative predictors of job performance, respectively. The study is able to raise awareness among the public on the importance of job performance in an organization and provide insight for relevant authorities to develop useful intervention programs to maintain or boost the job performance level among working adults